Blockchain for unity game applications - Cedric, Karuvallil Saji (Nanyang Technological University, 2023)
Serious games are gaining a lot of attention and investment due to their practicality. These games are usually made with the intention to educate, simulate certain virtual environments, or train players. Serious games are applicable to many organisations. Schools that want to educate their students, hospitals that want to monitor the condition of their patients’ mental health or even the police force training new police officers will find serious games extremely practical.